Broad‐scale patterns in plant diversity vary between land uses in a variegated temperate Australian agricultural landscape. (16th May 2014) - Schultz, Nick L.; Reid, Nick; Lodge, Greg; Hunter, John T.
Abstract Plant diversity is threatened in many agricultural landscapes. Our understanding of patterns of plant diversity in these landscapes is mainly based on small‐scale (<1000 m2) observations of species richness. However, such observations are insufficient for detecting the spatial heterogeneity of vegetation composition. In a case‐study farm on the North‐West Slopes of New South Wales, Australia, we observed species richness at four scales (quadrat, patch, land use and landscape) across five land uses (grazed and ungrazed woodlands, native pastures, roadsides and crops). We applied two landscape ecological models to assess the contribution of these land uses to landscape species richness: (i) additive partitioning of diversity at multiple spatial scales, and (ii) a measure of habitat specificity – the effective number of species that a patch contributes to landscape species richness. Native pastures had less variation between patches than grazed and ungrazed woodlands, and hence were less species‐rich at the landscape scale, despite having similar richness to woodlands at the quadrat and patch scale. Habitat specificity was significantly higher for ungrazed woodland patches than all other land uses. Our results showed that in this landscape, ungrazed woodland patches had a higher contribution than the grazed land uses to landscape species richness. These results have implications for the conservation management of this landscape, and highlighted the need for greater consensus on the influence of different land uses on landscape patterns of plant diversity.